Long-term RNA persistence in postmortem contexts - Fordyce, S.; Kampmann, M.; L van Doom, N.; Gilbert, Thomas (BioMed Central, 2013)
Ribonucleic acids (RNA) are generally considered fragile molecules that are readily degraded. However, there is growing documentation of long-term (from days to centuries) RNA persistence in a variety of contexts and tissue types, and as such a number of academic disciplines are beginning to exploit degraded RNA. While the reasons for its survival are not fully understood, there are several plausible mechanisms that would safeguard this molecule against degradation. However, after examining the literature available on the postmortem instability and decay mechanisms of RNA, it has become clear that limited experimental studies and no reviews offer an overview of these mechanisms. Hence in this review we outline molecular reasons for RNA surviving long-term postmortem, and provide specific examples of RNA survival in forensic, archival and archaeological contexts. A better understanding of the mechanisms of RNA decay will be crucial for developing expectations on its long-term survival.